Expressions of commonly used housekeeping proteins are altered in asthmatic mouse lungs - Abigail R. Patterson; Alexandra P. Crawford; Amanda S. Hatcher; Dovenia S. Ponnoth; Shinichi Asano (Biochemistry and Biophysics Reports)
Housekeeping protein expression in tissue samples is often used to normalize immunoblotting data. However, utilizing common loading control proteins in pathological conditions without validation can be problematic. Here, we describe the alteration of commonly used loading control protein expressions in asthmatic lung samples and present a simpler and more reliable loading control for western blot analysis. Lung samples from control and asthmatic mice groups were used to assess the expression levels of three commonly used housekeeping proteins (beta-actin, alpha-tubulin, and glyceraldehyde-3-phosphate dehydrogenase). Ponceau S staining data was also obtained to assess the consistency of protein loading. Housekeeping protein expressions varied dramatically in asthmatic groups, ranging from 26 to 278 % compared to the control group (p < 0.05). On the other hand, no significant differences in Ponceau S staining were observed among the groups. There were no differences in protein extraction from lung samples among the groups, but significant differences were observed in bronchoalveolar lavage leukocyte populations (p < 0.05). Our data suggest that lung resident immune cells were dramatically altered in asthma groups, and protein expression of commonly used loading control proteins are unreliable for western blot analysis of asthmatic lungs. We recommend Ponceau S staining as a more reliable loading control for asthmatic lung samples to normalize western blot data.